Efektivitas Penggunaan Herbisida Paraquat Dan Atrazin Terhadap Gulma Pada Jarak Tanam Jagung (Zea mays L.) Yang Berbeda - Nuzul Akram; Baidhawi Baidhawi; Rosnina Rosnina (Faculty of Agriculture, Universitas Malikussaleh, 2019)
This study aims to compare the active compound of Paraquat and Atrazine herbicides applied for weed controlling between plant spacing of corn. The research was conducted in Paya Beunyot Village, Banda Baro Regency North Aceh from July to September 2019, and continued with Samples analysis at the Agroecotechnology Laboratory, Faculty of Agriculture, Universitas Malikussaleh. The experimental design used was a factorial randomized block design; herbicides type of paraquat with a concentration of 1.38 kg/ha, atrazine concentration 1.2 kg/ha and the second factor were plant spacing (P): P1= plant spacing of 50x30 cm, P2= plant spacing of 60x25 cm, P3= plant spacing of 75x20 cm. The results showed that herbicide applied had a very significant effect on weed wet weight, dry weight, percentage of weeds under control and phytotoxicity of weeds. The results showed the interspace of the plant gave a very significant increase in seeds weight either per plant and per plot. The result of variance analysis showed there was no interaction between herbicides utilize and planting distance in all observed variables.Keywords; Corn (Zea mays L.), herbicide, plant spacing